COMMUNICATION ISSUES IN THE MOVIE “HIGH SCHOOL HIGH” - Mahan, Travis (Acta Scientiae et Intellectus, 2024)
This paper will explore the movie “High School High” (1996) written by David Zucker and Robert LoCash, and the communication aspects found within the movie. Individuals, especially those teaching in a diverse community, may carry their own biases and beliefs of different cultures into the classroom. As a result, the way they approach their relationships and teaching may not reach all of their students. There are three main areas of communication that will be covered in depth. These three will be communication and culture, listening skills, and nonverbal communication. All too often, there will be students that are misunderstood and go unnoticed in schools. They are overlooked for various reasons, and one of the main reasons is the teacher’s ability or inability to listen, and to communicate. One of the most important aspects of communication and one reason that students and people are misunderstood is because of nonverbal communication. People can tell how you are doing by the way you are standing, your body posture, or by facial expressions. There are many different aspects to effective communication, and these are just three areas that are important and are prevalent in the movie “High School High” and which will be examined and explored here.